2022
DOI: 10.3390/plants11202705
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Drought Tolerance of Elite Bread Wheat (Triticum aestivum L.) Genotypes Using Genome Wide Association Study in Morocco

Abstract: Drought is one of the most important yield-limiting factors in Morocco. Identification and deployment of drought-tolerant wheat varieties are important to cope with the challenge of terminal moisture stress and increase wheat productivity. A panel composed of 200 elite spring bread wheat genotypes was phenotyped for yield and agronomic traits for 2 years (2020 and 2021) in Morocco under rainfed and irrigated environments. The panel was genotyped using 20K SNPs and, after filtration, a total of 15,735 SNP marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Wheat is affected by drought stress at all growth stages. Even though most earlier studies focused on aboveground adult plant traits (El Gataa et al, 2022), seedling traits are equally important since the seedling stage is the most vulnerable stage in warm and dry regions, and their trait values may differ significantly from those of adult plants (Harrison and Laforgia, 2019). This study evaluated a bread wheat panel systematically assembled from the CIMMYT gene bank for seedling traits (viz., CL, SLT, RLT, SWT, and RWT) under hydroponics conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wheat is affected by drought stress at all growth stages. Even though most earlier studies focused on aboveground adult plant traits (El Gataa et al, 2022), seedling traits are equally important since the seedling stage is the most vulnerable stage in warm and dry regions, and their trait values may differ significantly from those of adult plants (Harrison and Laforgia, 2019). This study evaluated a bread wheat panel systematically assembled from the CIMMYT gene bank for seedling traits (viz., CL, SLT, RLT, SWT, and RWT) under hydroponics conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Drought tolerance is a complex quantitative trait governed by many genes, some of which have minor effects while others have major effects (Kumar et al, 2012). Further, it has low heritability owing to its polygenic inheritance and significant genotype by environment interaction (Sukumaran et al, 2018;El Gataa et al, 2022;Rabieyan et al, 2022). Drought tolerance can be improved genetically by identifying sources of stress-tolerant traits and/or genotypes, and introgressing and mobilizing the genomic regions controlling these traits into locally adapted cultivars (Shelake et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These QTLs were associated with [i] root and shoot attributes during the seedling stage and [ii] canopy temperature during the grain-filling stage. El Gataa et al [65] revealed noteworthy single-nucleotide polymorphisms [SNPs] among candidate genes associated with plant abiotic stress responses. These findings have the potential to facilitate marker-assisted selective breeding aimed at enhancing drought resistance at the seedling stage.…”
Section: Molecular Breeding For Drought Tolerance In Wheatmentioning
confidence: 99%
“…Some QTLs of wheat detected by Maulana et al [49] co-localized with previously reported QTLs (i) for root and shoot traits at the seedling stage and (ii) for canopy temperature at the grain-filling stage. Some significant single-nucleotide polymorphisms (SNPs) were identified in candidate genes involved in plant abiotic stress responses, which will allow marker-assisted selective breeding for drought tolerance at the seedling stage [50].…”
Section: Qtl Mapping For Drought Stress Tolerance In Plantsmentioning
confidence: 99%